2019
DOI: 10.3390/min9050310
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Organic Matter on Uranium Precipitation in Zoovch Ovoo, Mongolia

Abstract: The Zoovch Ovoo uranium deposit is located in East Gobi Basin in Mongolia. It is hosted in the Sainshand Formation, a Late Cretaceous siliciclastic reservoir, in the lower part of the post-rift infilling of the Mesozoic East Gobi Basin. The Sainshand Formation corresponds to poorly consolidated medium-grained sandy intervals and clay layers deposited in fluvial-lacustrine settings. The uranium deposit is confined within a 60- to 80-m-thick siliciclastic reservoir inside aquifer driven systems, assimilated to r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 42 publications
(58 reference statements)
0
21
0
Order By: Relevance
“…In addition, the maceral composition is an important factor in evaluating the coal seam quality. Precise identification of the maceral components has a multitude of uses across various industry sectors, including hydrogenation, combustion, carbonization and gasification [2][3][4].…”
Section: Background and Motivationmentioning
confidence: 99%
“…In addition, the maceral composition is an important factor in evaluating the coal seam quality. Precise identification of the maceral components has a multitude of uses across various industry sectors, including hydrogenation, combustion, carbonization and gasification [2][3][4].…”
Section: Background and Motivationmentioning
confidence: 99%
“…Vitrinite reflectance measurements in the Zoovch Ovoo sands led to %Rr=0.302±0.02 (Rallakis et al, 2019). Thus, it may be concluded that the highest temperature experienced by the dolomite cements can be estimated at about 40°C.…”
Section: Dolomite Burial Diagenesismentioning
confidence: 88%
“…In this tectonic framework, the burial history of the regional area of Zoovch Ovoo as well as the geothermal gradient (4.5°C/100m) were based on Graham et al (2001), Prost (2004), Rallakis et al (2019;.…”
Section: Stratigraphy Of the East Gobi Basinmentioning
confidence: 99%
“…The Central Asia Uraniferous Province, one of the most strategic areas in the world for uranium reserves, extends from Kazakhstan to the West towards the Transbaikal region to the East (Dahlkamp, 2009;Le Goux et al, 2015;IAEA 2018). Significant roll-front deposits exist all over this region, examples include the Chu-sarysu and Syrdarya basins in Kazakhstan (Aubakirov, 1998;Petrov 1998;Jaireth et al, 2008;Munara, 2012;Lach et al, 2015), the Songliao, Ordos and Erlian basins in China (Huang Xian-Fang et al, 2005;Min et al, 2005;Cai et al, 2007;Bonnetti et al, 2015a,b;Cao et al, 2016;Akhtar et al, 2017;Bonnetti et al, 2017;Jiao et al, 2018;Zhang et al, 2018;Yue et al, 2019) and the Unegt and Zuunbayan basins in Mongolia (Le Goux et al, 2015;Grizard et al, 2018;Boissezon et al, 2020;Rallakis et al, 2019;.…”
Section: Introductionmentioning
confidence: 99%